Autoantibody against 14-3-3 zeta: a serological marker in detection of gastric cancer - Qin, Jiejie; Wang, Shuaibing; Wang, Peng; Wang, Xiao; Ye, Hua; Song, Chunhua; Dai, Liping; Wang, Kaijuan; Jiang, Binghua; Zhang, Jianying (Journal of cancer research and clinical oncology, 2019)
Purpose Autoantibody to 14-3-3 zeta was identified in gastric cancer (GC) by serological proteome analysis (SERPA) in our previous study. We comprehensively evaluated its ability to detect GC, determined its association with clinical characteristics, and explored its temporal change in GC patients before and after gastrectomy resection in this study. Methods Anti-14-3-3 zeta antibody was examined by immunoassay in sera from 465 GC patients and 465 normal individuals, and also in 69 serial sera from 26 GC patients before and after resection. Results The frequency of anti-14-3-3 zeta were significantly higher in GC group than in control group, with AUC of 0.627. The appearance of anti-14-3-3 zeta showed no difference in different tumor stage, tumor size, tumor differentiation, and lymphatic metastasis, but was higher in GC patients with family tumor history than without family tumor history. When anti-14-3-3 zeta was combined with clinical markers (CEA, CA199 and CA724), the sensitivity increased to 52.7%. In the follow-up analysis, the titer of anti-14-3-3 zeta was higher in post-resection sera than pre-resection sera, and no difference was observed in CEA, CA199 and CA724. Anti-14-3-3 zeta showed an increase from negative status to positive status in six patients after resection, while other three clinical markers presented different change in GC patients after resection. Conclusions Autoantibody against 14-3-3 zeta could be a potential diagnostic biomarker and improve the sensitivity of CEA, CA199 and CA724 in diagnosis of GC. Further largescale studies will be needed to validate its performance in GC patients after resection.